Non-respiratory health risks and mortality associated with fighting bushfires (wildfires): a systematic review - Asmare Gelaw; Win Wah; Deborah C. Glass; Malcolm R. Sim; Ryan Hoy; Janneke Berecki-Gisolf; Karen Walker-Bone (International Archives of Occupational and Environmental Health, 2025)
Background Bushfires (also known as wildland or forest fires) expose emergency responders to occupational hazards under exceptional circumstances. Whilst the health impacts of structural firefighting have been studied, less is known about the non-respiratory health impacts or risk of mortality amongst bush firefighters, who can be volunteers. More information about health risks is needed to generate effective prevention strategies. Objective To critically evaluate and synthesise the published evidence about the non-respiratory health risks and risk of mortality associated with bushfire fighting. Methods A systematic literature search was conducted in Medline, Scopus, and Embase to identify studies evaluating morbidity or mortality or associated risk factors among bushfire fighters. The quality of included studies was evaluated twice independently using a specific quality assessment tool. Results Twenty-seven studies were included. 11(41%) were assessed as moderate quality and 16(59%) as low quality. There is a growing body of evidence for adverse short-term impacts of bushfire fighting on mental health and injuries. Linkage studies showed that volunteer firefighters had lower mortality and cancer risk in their late forties compared to the general population. Conclusion Most studies relied on cross-sectional and retrospective designs without comparison groups, limiting the ability to draw robust conclusions. It is essential to conduct higher-quality research using prospective designs and longer-term follow-up to better understand the health outcomes of bushfire fighting, particularly given the anticipated increase in the frequency and severity of bushfires.

Systematic review of impacts of occupational exposure to wildfire smoke on respiratory function, symptoms, measures and diseases - Win Wah; Asmare Gelaw; Deborah C. Glass; Malcolm R. Sim; Ryan F. Hoy; Janneke Berecki-Gisolf; Karen Walker-Bone (International Journal of Hygiene and Environmental Health, 2025)

Impact of extreme bushfire seasons on rates of occupational injury and disease compensation claims in first responders - Win Wah; Janneke Berecki-Gisolf; Deborah C. Glass; Ryan F. Hoy; Malcolm R. Sim; Alex Collie; Karen Walker-Bone (International Archives of Occupational and Environmental Health, 2024)